The Influence of Competency on Employee Productivity: A Systematic Literature Review on the Roles of Motivation and Recruitment Analysis - Rachman, Faizal; Rony, Zahara T. (Dinasti Publisher, 2026)
Employee productivity remains a critical issue for organizations facing increasing competition and rapid environmental change. Prior studies indicate that employee competency plays a central role in enhancing productivity; however, the mechanisms through which this relationship operates remain fragmented. This study aims to systematically review international empirical research examining the influence of employee competency on employee productivity, with motivation and recruitment analysis as additional explanatory variables. A Systematic Literature Review (SLR) was conducted using the PRISMA model to ensure transparency and methodological rigor. Ten international journal articles published between 2015 and 2024 were selected from reputable databases, including Scopus and Google Scholar. The findings indicate that competency consistently demonstrates a strong positive relationship with employee productivity. Motivation frequently acts as a mediating mechanism that strengthens the competency–productivity link, while recruitment analysis functions as an upstream organizational practice that ensures competency alignment and productivity sustainability. This review contributes by integrating competency, motivation, and recruitment analysis into a unified conceptual framework for employee productivity. The study offers theoretical implications for human resource management literature and practical guidance for organizations seeking to enhance workforce productivity through strategic recruitment, competency development, and motivational systems.